2011
DOI: 10.1083/jcb.201011119
|View full text |Cite
|
Sign up to set email alerts
|

Actomyosin II contractility expels von Willebrand factor from Weibel–Palade bodies during exocytosis

Abstract: High-resolution microscopy reveals how discrete actin cytoskeletal functions inhibit or promote specific exocytic steps during regulated secretion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
185
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(201 citation statements)
references
References 58 publications
11
185
1
3
Order By: Relevance
“…Furthermore, it was found that to release the content of these vesicles, Myosin2a and 2b recruitment and activity were required to provide the contractile force necessary to complete fusion of the vesicle with the plasma membrane (Masedunskas, et al, 2011). Similar observation has been reported for the secretion of von Willebrand factor from human endothelial cells (Nightingale, et al, 2011).…”
Section: Phospho-regulation Beyond Fusionsupporting
confidence: 60%
“…Furthermore, it was found that to release the content of these vesicles, Myosin2a and 2b recruitment and activity were required to provide the contractile force necessary to complete fusion of the vesicle with the plasma membrane (Masedunskas, et al, 2011). Similar observation has been reported for the secretion of von Willebrand factor from human endothelial cells (Nightingale, et al, 2011).…”
Section: Phospho-regulation Beyond Fusionsupporting
confidence: 60%
“…The ability of a cell to achieve a complex, polarized architecture also relies on actomyosin contractility (Lee et al, 2012;Walters et al, 2006;Yu et al, 2008) as does its ability to migrate (Aguilar-Cuenca et al, 2014;Vicente-Manzanares et al, 2009). Moreover, actomyosin contractility regulates several aspects of endosome organization and trafficking (Chandrasekar et al, 2014;Lynch et al, 2013;Masedunskas et al, 2011;Nightingale et al, 2011;Olazabal et al, 2002;Zilberman et al, 2011).…”
Section: Cellular Functions Of the Contractomementioning
confidence: 99%
“…To better understand drug-packaging MP-mediated tumour cell killing, the mechanism involved in tumour cell release and uptake of MPs was investigated. The cytoskeleton has important roles in cellular endocytosis and exocytosis [23][24][25][26] , leading to the possible requirement of cytoskeletal proteins for the release and uptake of MPs by tumour cells. When H22 cells were treated with cytochalasin D, an inhibitor of F-actin polymerization, actin filament formation was inhibited, resulting in decreased MP release, induced by ultraviolet irradiation (Fig.…”
Section: Cisplatin-encapsulating Mps Inhibit Ovarian Cancer Growthmentioning
confidence: 99%